Metal-free ring expansion of indoles with nitroalkenes: a simple, modular approach to 3-substituted 2-quinolones1. Issue 12 (11th February 2015) - Aksenov, Alexander V.; Smirnov, Alexander N.; Aksenov, Nicolai A.; Aksenova, Inna V.; Matheny, Jonathon P.; Rubin, Michael
<x xml:space="preserve">Abstract</x> 3-Substituted 2-quinolones are obtained via a novel metal-free transannulation reaction of 2-nitroolefins with 2-substituted indoles in polyphosphoric acid.